Le mémoire comme outil d'appréciation des attentes et des besoins en accompagnement en formation à distance - Elizabeth Armao Méliet (Centre National d'Enseignement à Distance, 2016)
Distance learning reveals a number of uncertainties: the learner must be able to show some degree of autonomy and cope with this very feeling of uncertainty (Brugvin, 2005; Jézégou, 1998). Our research will be based on the writings of Emile Durkheim (1930), Robert Castel (2009), Alain Ehrenberg (1995) and Edgar Morin (2000), so as to justify our definition of the notion of uncertainty. High-level athletes are confronted to uncertainty on a regular basis and throughout their whole career (Lévèque, 2008) without however being prepared to face it outside of the competitive background (UNCU and USJSF, 2004). In what way are the tools for mediation (Peraya, 1999) able to help the protagonists of the framework of accompaniment to face this phenomenon in the context of distance learning? In order to answer this question, we have interviewed five high-level athletes -who were in the process of distance learning and enrolled in level-II degree courses- regarding their experience with the process of accompaniment throughout learning, especially the writing of their dissertation. The elaboration of the dissertation seems to constitute an essential tool to appreciate the relation of the learner with the framework and allows us to elaborate a accompaniment which is negotiated and adapted to his project.